2021
DOI: 10.3906/kim-2012-7
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of melatonin under heavy metal-induced stress in Melissa Officinalis L.

Abstract: Heavy metals, due to their inability to degrade, pose a serious environmental and nutritional problem. The accumulation of essential and non-essential heavy metals in living organisms reduces normal growth and development, resulting in acute poisoning, disease and even death of organisms. Melatonin is a very important multifunctional molecule in protecting plants from oxidative stress due to its ability to directly neutralize reactive oxygen species (ROS). Also, melatonin has a chelating property, which may co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…It has been shown that the external treatment of ML increases the level of internal ML by enhancing the level of enzymatic and non-enzymatic antioxidants through stimulating the expression of their biosynthesizing genes, diminishes the level of free radicals and ROS, and maintains redox homeostasis under stressful conditions [ 40 ]. Similar results of the induction effects of ML on enhancing the activity of antioxidant enzymes and reducing the endogenous level of ROS under salinity [ 39 ], cold [ 41 ], and heavy metal [ 12 ] stresses have already been documented, which confirms the role of ML in enhancing the plant’s antioxidant defense system. Therefore, these results prove that external application of ML can enhance the antioxidant defense system in NaCl-stressed Paneer-booti plants, which may play a significant function in improving plant tolerance by reducing ROS levels and protecting membrane lipids.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It has been shown that the external treatment of ML increases the level of internal ML by enhancing the level of enzymatic and non-enzymatic antioxidants through stimulating the expression of their biosynthesizing genes, diminishes the level of free radicals and ROS, and maintains redox homeostasis under stressful conditions [ 40 ]. Similar results of the induction effects of ML on enhancing the activity of antioxidant enzymes and reducing the endogenous level of ROS under salinity [ 39 ], cold [ 41 ], and heavy metal [ 12 ] stresses have already been documented, which confirms the role of ML in enhancing the plant’s antioxidant defense system. Therefore, these results prove that external application of ML can enhance the antioxidant defense system in NaCl-stressed Paneer-booti plants, which may play a significant function in improving plant tolerance by reducing ROS levels and protecting membrane lipids.…”
Section: Discussionsupporting
confidence: 78%
“…In addition to the role of ML as an antioxidant, it has been shown that ML has the ability to regulate the expression of genes involved in important plant metabolisms [ 8 , 11 ]. The beneficial effects of ML on the tolerance of plants under drought [ 7 ], heavy metal [ 12 ], cold [ 13 ], and salt [ 9 ] stress have been reported, which indicates the role of ML in inducing the plant’s defense mechanism under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, exogenous amino acids (e.g., Pro, gamma-aminobutyric acid, and glutamate) can minimize heavy metal toxicity in rice, tomato, and brinjal ( Jiang et al, 2020 ; Suhel et al, 2022 ; Zhang et al, 2022 ) by mediating the transcription factors and the antioxidant systems. Additionally, exogenous plant hormones (e.g., JA, auxin, kinetin, and melatonin) can regulate metal uptake, photosynthetic pigments, and antioxidant systems to enhance stress resistance ( López et al, 2007 ; Wang et al, 2015 ; Dai et al, 2020 ; Hodžić et al, 2021 ). In this study, we displayed the effects of exogenous Pro on ATH accumulation through regulating Jasmonate signals and MYB-bHLH-WDR complex and protecting rice plants from Cr(VI) stress.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed that, under various abiotic stresses, the melatonin-mediated ascorbate–glutathione (AsA–GSH) cycle serves a crucial role in scavenging reactive oxygen species in cells ( Xie et al., 2022 ; Zhang et al., 2022 ). Specifically, melatonin enhances the AsA/DHA and GSH/GSSG ratios and antioxidant capacity by stimulating the AsA–GSH cycle, thereby improving the scavenging capacity of ­O 2 · − and ­H 2 O 2 , reducing oxidative stress and providing an approach to reduce organic residues through plant detoxification mechanisms ( Dong et al., 2018 ; Hodžić et al., 2021 ; Yan et al., 2022 ). In addition, melatonin could make a direct connection with various oxidizing agents, particularly with hydroxyl radicals, to reduce the damage to cell structures (one molecule of melatonin neutralizes a maximum of 10 molecules of ROS/RNS) ( Simlat et al., 2018 ; Kyoungwhan, 2021 ).…”
Section: Melatonin Functions Against Abiotic Stressmentioning
confidence: 99%